Multilocus Genotyping Indicates that the Ability To Invade the Bloodstream Is Widespread among Candida albicans Isolates - Luu, Lien N. (American Society for Microbiology, 2001)
Multilocus genotyping was used to compare populations of Candida albicans from oral mucosa and blood. No significant differences in allele frequencies between the two samples were detected, and in a dendrogram of genotypic similarities, genotypes from both types of samples were finely interspersed. This is evidence for widespread distribution of invasive potential.